A new allelic discrimination real-time PCR assay for PavMYB10.1 genotyping to predict sweet cherry fruit colour: a comparison with the Pav-Rf-SSR assay. Issue 2 (4th March 2021) - Cmejla, Radek; Zdarska, Ivona; Suran, Pavol; Paprstein, Frantisek; Cmejlova, Jana
ABSTRACT: Fruit skin colour in cherries (Prunus avium L.) is one of the most important market characteristics with customer preferences varying across cultures and countries. Based on skin colour, cherries can be divided into three market classes: yellow, blush, and mahogany. The PavMYB10.1 gene has been recently shown to be a key player in fruit colouration, and three alleles ( PavMYB10.1a [WT(5A)]; PavMYB10.1b [Mut(4A)]; and PavMYB10.1c [InDel]) have been associated with cherry skin colour. In the present study, an allelic discrimination real-time PCR assay was developed for marker-assisted selection (MAS). The Pav-Rf -SSR assay that had previously been described for colour prediction was also employed for comparison. Both assays were used to screen 302 phenotyped accessions in a germplasm collection. The real-time PCR assay reliably discriminated all six PavMYB10.1 genotypes, and accurately predicted skin colour in all PavMYB10.1 homozygous genotypes; however, for heterozygotes, the assay was uninformative. As for the Pav-Rf -SSR assay, only two out of six observed alleles were informative, and only for mahogany market class. Using combined approach, fruit skin colour could be successfully predicted in 67.9% of all germplasm samples. The real-time PCR assay for PavMYB10.1 genotyping thus represents suitable tool for laboratories interested in MAS for skin colour in sweet cherries.